1986
DOI: 10.1002/app.1986.070310632
|View full text |Cite
|
Sign up to set email alerts
|

Melt viscosity and electrical conductivity of carbon black‐PVC composite

Abstract: The effect of the structure of carbon black aggregates on the melt behavior and electrical conductivity of carbon black‐vinylchloride‐vinylacetate copolymer systems was analyzed. As the amorphous carbon aggregates are roll‐milled, they become cylindrical, then, as the milling time is prolonged, spherical. During milling, polymer adsorption and dispersivity increases in the same manner, causing the viscosity of the composite to decrease. It was established that during a certain milling time, conductivity rises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Therefore, the electrical conductivity threshold percolation concentration is about 6 phr in this rigid PVC/CB system and much lower than those of reported results. [11][12][13] That is based on the fact that the conductive CB with mean diameter of 30 nm are sufficient to come into contact with one another as the filler loading exceeds the threshold concentration. 24 This means when the CB is present in abundance in the PVC matrix, the PVC will be saturated with CB, which forms tunnels of electrons between adjacent carbon clusters and through the PVC matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the electrical conductivity threshold percolation concentration is about 6 phr in this rigid PVC/CB system and much lower than those of reported results. [11][12][13] That is based on the fact that the conductive CB with mean diameter of 30 nm are sufficient to come into contact with one another as the filler loading exceeds the threshold concentration. 24 This means when the CB is present in abundance in the PVC matrix, the PVC will be saturated with CB, which forms tunnels of electrons between adjacent carbon clusters and through the PVC matrix.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the molding pressure impacted the electrical conductivity of the composite very much. Noguchi et al 11 studied that the effect of the structure of CB aggregates on the melt behavior and electrical conductivity of poly(vinylchloride-co-vinylacetate)/CB composites. They found that the electrical conductivity of the composite was increased as the milling time was increased up to 30 min, then the electrical conductivity was decreased as the milling time was longer than 30 min.…”
Section: -8mentioning
confidence: 99%
“…Figure 1(a) also shows the influence of frequencies on the dielectric constant of the composites. This means that at lower frequencies of from 1 to 500 kHz, a steep increase in dielectric properties can be noticed compared to higher frequency ranges (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The increase in dielectric behavior at a higher dosage of carbon black loading is due to an increase in filler-filler interaction.…”
Section: Tensile Propertiesmentioning
confidence: 88%
“…Viscoelastic behavior of CB‐filled polymer has been one of the focuses in the field of particles‐filled polymeric materials 11–15. A phenomenon, so‐called “second plateau,” that the dynamic viscoelastic functions, e.g., storage modulus ( G ′) and loss modulus ( G ″), are independent of frequency (ω) at very low frequencies (terminal region), has been thought to be an important information concerning viscoelastic behavior of multicomponent polymer systems.…”
Section: Introductionmentioning
confidence: 99%